Comparison on incidence, radiological features and outcome of skull base versus non-skull base meningioma in General Hospital Kuala Lumpur : a 5-year retrospective study - Kong, Chan Chee (2016)
Background: Meningiomas are the most common intracranial tumours, accounting for 13-26% of all the primary intracranial tumours. In the United States, an estimated 2–3% of the population has an incidental asymptomatic meningioma, and annual incidence of symptomatic meningioma is 2 cases per 100,000 individuals. Skull base meningiomas comprise 30% of meningiomas and are one of the most difficult intracranial tumours to be managed surgically because of the difficulty in approaching the lesions and their proximity to vital structures such as cranial nerves and major blood vessels. Meningiomas are commonly seen in Malaysia, however there is minimal local data published. The main purpose of our study was to identify the demographic data, tumours characteristic and surgical outcome of patients with meningiomas operated in GHKL. Methods: A total of 199 patients with histologically proven meningiomas were operated from January 2010 till December 2014 in General Hospital Kuala Lumpur. They were categorized into skull base and non-skull base groups. Demographical data, tumour characteristics and patients’ outcome were studied. Kaplan-Meier overall survival curve and Cox hazard univariable and multivariable regression for possible predictors of survival were analyzed. Results: There was 199 patients included in the study, 97.5% of the patients (n=194) had WHO grade I meningioma Only 5 patients had WHO grade II meningiomas. However, no new WHO grade III meningiomas diagnosed throughout the study period. Majority of our patients were female (n=134; 67.3%) with only 65 patients were male (32.7%). Malay ethnicity has the highest incidence (n=138; 69.3%). Skull base meningioma (n=54) comprised 27.1 % of all the intracranial meningioma. Majority of the skull base meningiomas were histopathologically WHO grade I (n=52, 96.3%). Seventy percent of the skull base meningioma group was female (n=38) with mean age at diagnosis was 51.7 (SD 11.01), as compared to non-skull base group with mean age of diagnosis at 54.1 (SD 9.4). Both categories showed highest prevalence in age group 40-60 with skull base group (n=33; 61.1%) and non-skull base group (n=91; 62.8%). Majority of the patients in both skull base and non-skull base group presented with clinical feature of headache, with 94.4% (n=51) and 91% (n=132) respectively. Radiologically, ninety four percent of the patients with skull base meningioma (n=51) had radiological evidence of oedema; 30 cases (55.6%) had hyperotosis and 16 patients (29.6%) had calcification as reported by radiologists. Skull base meningioma was related to poorer outcome with poor discharge condition (n=23; 42.6% p value < 0.01) and higher possibility of incomplete resection (n=34; 63% p value < 0.01). In contrast, 88% (n=128) patients in non-skull base meningiomas group were discharged well and only 11 cases out of the total 145 patients were incompletely resected. Our study showed a shorter median survival of 37.6 months (SD 20.94) for skull base group as compared to 47.8 months (SD 18.2) in the non-skull base group with p-value 0.187. Multivariate cox hazard regression test showed skull base meningioma group had 4 times the chance to succumb to death as compared to non-skull base group (Adjusted HR 4.22; 95% CI 1.53-11.66; p-value 0.005), adjusted with gender, comorbidities, WHO grading and extends of meningioma. Conclusion: The primary treatment for symptomatic meningioma is surgery, which can be curative if the tumour is completely removed. Skull base meningiomas are widely accepted as being more technically challenging to achieve gross total resection. Our study has showed skull base meningiomas operated locally had higher rate of incomplete resection and poorer surgical outcome as compared to non-skull base group. Patients with skull base meningioma had 4 times higher risk to succumb to death as compare to non-skull base group. More studies need to be carried out locally to look into skull base meningioma seriously for the improvement of surgical outcome